Leukocyte cell derived chemotaxin-2 (Lect2) as a predictor of survival in adult acute liver failure - Slowik, Voytek; Borude, Prachi; Jaeschke, Hartmut; Woolbright, Benjamin L.; Lee, William M.; Apte, Udayan; Failure Study Group, the Acute Liver (Translational Gastroenterology and Hepatology, 2019)
Background: One of the major issues in the field of acute liver failure (ALF) is the lack of reliable biomarkers that predict outcome. Many cases present with very limited treatment options and prognostic indicators are invaluable. We tested whether leukocyte cell derived chemotaxin 2 can be used as a prognostic biomarker to predict patient survival either alone or in combination with other routine clinical parameters. Methods: Serum samples and associated clinical data from came from two independent sources, the Acute Liver Failure Study Group (ALFSG) registry and the University of Kansas Medical Center. We analyzed a total of 61 cases, each with individual time points collected over a period of 0 to 7 days after hospital admission. Analysis was developed to compare responses in survivors vs. non-survivors. Results: The data indicate that survivors had significantly lower serum levels of leukocyte cell derived chemotaxin 2 compared to non-survivors (P=0.03). Further, it was able to predict patient survival when taken together with either international normalized ratio (INR) alone (71% concordance) or INR and bilirubin (76% concordance) or INR and serum albumin (77% concordance). Furthermore, when we analyzed data for each day, serum Lect2 and INR taken together were able to predict survival at day three after hospital admission with 86.3% concordance. Conclusions: These studies have revealed test batteries consisting of easily available serum tests that are concordant with survival status of ALF patients early during the clinical course.